2008
DOI: 10.1243/09544119jeim357
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the measured and predicted flowfield in a patient-specific model of an abdominal aortic aneurysm

Abstract: Numerical simulation is increasingly being used to predict the flowfield within patient-specific geometries of abdominal aortic aneurysms under physiologically realistic flow conditions. This paper reports on a comparison between the flowfield measured in vitro within a patient-specific model of a mature abdominal aortic aneurysm and that predicted using computational fluid dynamics (CFD). Visualization and traverses of axial velocity were obtained at a number of locations in the aneurysm region under both ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Their findings implicate that the resistance to blood flow decreases as the diameter of an aneurysm increases, and in practical purposes, turbulence is not a significant factor. Although they adopted a computational fluid dynamics method in their analysis, it is reported to agree well with the realistic measurements [19]. From the fluid dynamics point of view, an aneurysm is like the development of collateral circulations in terms of cause and effect; actually, they commonly occur together [5,8].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Their findings implicate that the resistance to blood flow decreases as the diameter of an aneurysm increases, and in practical purposes, turbulence is not a significant factor. Although they adopted a computational fluid dynamics method in their analysis, it is reported to agree well with the realistic measurements [19]. From the fluid dynamics point of view, an aneurysm is like the development of collateral circulations in terms of cause and effect; actually, they commonly occur together [5,8].…”
Section: Discussionmentioning
confidence: 72%
“…This study showed that CA stenosis and PDA aneurysm can provoke each other in reverse directions. CA stenosis provokes PDA aneurysm by increasing PDA flow if it is already compromised with wall tension-weakening conditions such as segmental arterial mediolysis, Marfan syndrome, or atherosclerosis [3,19]. Conversely, PDA aneurysm and/or arterial collaterals can provoke CA stenosis by decreasing CA flow if it is already compromised by wall tension-increasing conditions such as median arcuate ligament syndrome or atherosclerosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…14 The methodology used to obtain the images has been reported in detail previously. 12 However, in the interest of completeness, the technique is briefly summarised as follows. Neutrally buoyant 50 mm particles were (7) introduced to the flow and illuminated by a laser light sheet generated from a 100 mW argon ion laser.…”
Section: Velocity Fieldmentioning
confidence: 99%
“…The patient-based geometries described in this article were selected and generated by Dr James McCullough during work carried out in Dartmouth College, Hanover, NH. 20,21 Secured release was obtained from the patients involved. For each geometry, computerised tomography (CT) was used to produce a series of overlapping slices of 2.5 mm thickness.…”
Section: Geometry Creationmentioning
confidence: 99%